(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure effective teaching of business subjects at the public secondary school level inAkwa IbomState inspired thisstudy. Three researchquestionsguided the studyanda null hypothesis was tested at 0.05 level of significance. Descriptive survey research design was used for the study. A population of 235 principals from all public secondary schools in the area was studied without sampling because the size was manageable. An 18-item questionnaire with five response options was used for data collection. The instrument was validated by three experts. The reliability of the instrument was established using Cronbach Alpha correlation coefficient value of 0.87. Data collected were analyzed with mean for the research questions, and whilst student ttest was for testing the null hypothesis. Findings of the study showed that business teachers are effective in the three professional teaching competencies. It was also found that gender significantly influenced the opinions of the respondents and the null hypothesis was rejected. It was recommended, among others, that: secondary school business subjects’ teachers should attend short courses and conferences to update and upgrade their professional teaching competencies; and that government should adequately fund education for effective teaching of business subjects.